Edukasi Manajemen Diri Menggunakan Media Leaflet pada Keluarga dengan Gastritis Kabupaten Cianjur - Ricko Dwi Haryanto; Asep Suryadin; M Ikhsan (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Gastritis is a disease that occurs in everyone, whether children, adults or the elderly, which occurs in the digestive system. Gastritis is an inflammatory process in the mucosal and submucosal layers of the stomach. The incidence of gastritis increases with the advancing process of aging. in this research, namely implementation using leaflet media. This research aims to determine the level of family knowledge about gastritis using leaflet media in the work area of the Community Health Center in Cianjur Regency. The design of this research is descriptive, this research aims to describe the level of family knowledge using leaflet media about gastritis in the working area of the Community Health Center in Cianjur Regency. A sample of 21 respondents was taken using total sampling technique. Data were obtained using a closed ordinal scale questionnaire. After the data is collected, the data is then processed using editing, scoring and tabulating methods. The research results showed that more than half of the 17 respondents from each family (88.4%) experienced a lack of knowledge of compliance. For this reason, it is hoped that health services in the working area of the Cianjur District Health Center will provide health education or counseling about gastritis to the families of patients who have a history of gastritis so that they can increase family knowledge about gastritis in the family.